Accidental dural puncture in obstetric patients and long term symptoms. Issue 6882 (3rd April 1993) - MacArthur, C; Lewis, M; Knox, E G
Abstract : OBJECTIVE–To examine the association between accidental dural puncture and long term headache and related symptoms. DESIGN–Postal questionnaire survey to elucidate new symptoms occurring after childbirth, and linking of these to data in obstetric and anaesthetic case notes. Women were surveyed between 13 months and nine years after delivery. SETTING–Birmingham Maternity Hospital. SUBJECTS–4700 women who had delivered their most recent baby under epidural anaesthesia, 74 of whom had suffered an accidental dural puncture. MAIN OUTCOME MEASURES–Frequencies of new headache or migraine or neck ache starting within three months after childbirth and lasting over six weeks. RESULTS–Among the 74 women who had had an accidental dural puncture there were 17 (23%) who reported one or more of the above symptoms. By comparison, among those who had had an epidural anaesthetic but no recorded puncture, only 329 (7.1%) reported these symptoms. The duration of the headache or migraine or neck ache in the dural tap group ranged from nine weeks to over eight years. Ten of these women reported still unresolved symptoms. CONCLUSIONS–Conclusions on causality were tentative. Most women would remember a dural tap, and this might influence their reporting of subsequent symptoms attributable to the event. In addition, detailed characterisation of the symptoms was not available. Nevertheless, the findings provide a clear indication of the need for further study of the possible long term sequelae of accidental dural puncture.